GOALS-JWST: Unveiling Dusty Compact Sources in the Merging Galaxy IIZw096 - Hanae Inami; Jason Surace; Lee Armus; Aaron S. Evans; Kirsten L. Larson; Loreto Barcos-Munoz; Sabrina Stierwalt; Joseph M. Mazzarella; George C. Privon; Yiqing Song; Sean T. Linden; Christopher C. Hayward; et al. (The Astrophysical Journal Letters, 2022)
We have used the Mid-InfraRed Instrument (MIRI) on the James Webb Space Telescope (JWST) to obtain the first spatially resolved, mid-infrared images of IIZw096, a merging luminous infrared galaxy (LIRG) at z = 0.036. Previous observations with the Spitzer Space Telescope suggested that the vast majority of the total IR luminosity ( L _IR ) of the system originated from a small region outside of the two merging nuclei. New observations with JWST/MIRI now allow an accurate measurement of the location and luminosity density of the source that is responsible for the bulk of the IR emission. We estimate that 40%–70% of the IR bolometric luminosity, or 3–5 × 10 ^11 L _⊙ , arises from a source no larger than 175 pc in radius, suggesting a luminosity density of at least 3–5 × 10 ^12 L _⊙ kpc ^−2 . In addition, we detect 11 other star-forming sources, five of which were previously unknown. The MIRI F1500W/F560W colors of most of these sources, including the source responsible for the bulk of the far-IR emission, are much redder than the nuclei of local LIRGs. These observations reveal the power of JWST to disentangle the complex regions at the hearts of merging, dusty galaxies.